Rita, Sue and Bob Too Based on a Play by Andrea Dunbar - Dunbar, Andrea (BFI, 2017)
Following an acclaimed career in hard-hitting TV drama, director Alan Clarke achieved a cinema hit with this much-loved comedy. Bradford teenagers Rita and Sue regularly babysit for successful couple Bob and Michelle, whose comfortable suburban lifestyle contrasts with their own bleak existence. One evening when Bob is taking them home, he suggests a detour to the moors. Impressed by his flashy car and worldly ways the girls are smooth-talked into a three-way sexual relationship that becomes very much part of their lives. At first it's a bit of laugh but people are quick to point the finger and the affair is soon out in the open. The screenplay was adapted from a series of acclaimed plays by Andrea Dunbar, which were based on her own upbringing on Bradford's Buttershaw council estate. The contrast of bawdy laughs with astute social comment results in one of the more memorable and enduring British films from the period. [www.bfi.org.uk]